The Design and Construction of a Bolometer. - Twizerimana, Julliet (Kabale University, 2023)
This project on the design and construction of a bolometer is conducted in October 2020 at Kabale University in Kabale district, Southwestern Uganda. A blackened platinum strip of a zigzag form as the heat sensitive element will be connected in a Wheatstone bridge with different resistors and a galvanometer will be used for the study aimed at investigating the effect of thermal /heat radiation on the resistance of the platinum strip or the bolometer. Galvanometer readings will be obtained and recorded. Keywords: Design, Construction, Bolometer.